Formulation of a functional probiotic, protein and energy drink beverage based on mago pulp and whey - Montenegro, Areli (2025)
Childhood malnutrition and anemia constitute a serious public health problem, driving the search for foods enriched with protein and vitamin supplements to help reduce this issue. In this context, the present research was developed with the objective of creating a protein rich, probiotic, and energy boosting becerage based on mango (Mangifera indica), whey, and Lactobacillus casei. Five treatments were formulated with different proportions of mango pulp and whey (T1: 90/10, T2: 70/30, T3: 50/50, T4: 30/70, and T5: 10/90, with two replicates per treatment. The bererages were inoculated with L. casei, and the pH was monitored every 48 hours for 14 days. Aprogessive decrease in pH from 5.0 - 6.0 to aproximately 4.0 was observed, demonstrating the viability and stability of the probiotic during storage. Regarding protein composition, treatment T5 reached 4.92 g/100 ml of protein, while treatments T1 througth T4 showed average values of 2.76 to 2.99 g/100ml. For sensory analysis, a satisfaction survey was administered to 70 panelists, who evaluated aroma, color, flavor, and sweetness. According to the results, treatment T2 was the most favored by the tasters.